EVALUASI STRUKTUR DASAR PROGRAM KEAHLIAN (C2) DAN KOMPETENSI KEAHLIAN (C3) PADA KURIKULUM SMK KIMIA ANALISIS 4 TAHUN - Asep Nugraha, - (2021)
Research on the evaluation of the basic structure of the expertise program (C2) and skill competence (C3) in the 4-year analytical chemistry vocational school curriculum aims to obtain empirical and comprehensive information about the synchronization value of the basic structure of the expertise program (C2) and expertise competence (C3) in the SMK chemistry curriculum 4-year analysis of government regulatory policies in vocational education governance, the Indonesian national work qualification and the competency needs of the industrial world as an effort to link and match with industrial skills in implementing a shift in the employment paradigm towards updating skills/employability. The study was conducted with a discrepancy evaluation approach through qualitative-quantitative (mixed methods) applications of the exportative sequential design method. The results of the discrepancy analysis are as follows: 1) sequence: there is an overlapping sequence of the conceptual and procedural stages; 2) continuity: dominant in basic material; 3) integration: supporting materials for calibration and microbiology are needed; 4) scope: the development of aspects of character attitudes is still considered weak; 5) work attitude: it is necessary to have material legal knowledge of the field of expertise; 6) work role: there has been no implementation of the character of responsibility for other people's work; 7) Achievement of competencies: there needs to be strengthening of basic competencies and instruments; 8) demands for soft skills: there has been no implementation of a confident character; and 9) hard skills: on the competence of chemical instruments and basic analysis. In general, the basic structure of the expertise program (C2) and skill competence (C3) in the 4-year analytical chemistry vocational school curriculum is assessed according to the criteria for vocational governance, 3rd Indonesian national work qualification level and industry needs with a 70.3 matrix of a scale of 100.